1996
DOI: 10.1089/end.1996.10.169
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ureteral Stents after Endopyelotomy

Abstract: Despite the widespread practice of endopyelotomy for the management of ureteropelvic junction obstruction, the optimal conditions for ureteral healing after endoincision remain largely untested. Current recommendations for the use of large-caliber graduated endopyelotomy stents and a 6-week duration of stenting are being challenged by recent reports of successful outcomes with the use of standard, small-caliber ureteral stents and early stent removal. Moreover, improvements in stent design have led to the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The different studies which consider stent size after ureteral incision have not shown a significant advantage of larger over smaller stents [9,14,15] . However, it is possible to extract a series of conclusions from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different studies which consider stent size after ureteral incision have not shown a significant advantage of larger over smaller stents [9,14,15] . However, it is possible to extract a series of conclusions from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller stents [19] . In various studies, the groups with larger stents were associated with increased periureteral fibrosis and stricture formation, though without statistical significance [9,14] . Larger stents have been shown to be significant factors for patient discomfort [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 4-6 weeks of stenting after endopyelotomy is the standard clinical practice [3]. This recommendation is based on Davis' early work with intubated ureterotomy using the dog model [1], According to Davis, restoration of the muscular layer of the ureter takes at least 6 weeks [1], However, it is unclear whether the stent needs to remain in place for the entire duration of this healing phase.…”
Section: Discussionmentioning
confidence: 99%
“…The size of this stent must therefore allow effective urine diversion and healing of the ureter with an adequate caliber. However, no consensus regarding this 'ideal endopyelotomy stent' has yet been reached [3]. In a recent heterogeneous clinical series of endopyelotomies and endoureterotomies managed with either a 6 F inter nal stent or a 14/7 F endopyelotomy stent, the difference in success rates between the two groups was not statistical ly significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation